Analisa & Evaluasi Sistem Pembelian, Persediaan & Penjualan Tunai pada PT. ZRB - Kriswanto Kriswanto; Ririn Febrina (Binus Business Review, 2014)
Information technology is an important part of the company. With the application of information technology, the enterprise information system will be integrated well, so this will help the business processes within the company, and it is also expected to assist management in controlling the procedures performed by the staff. The problems faced by this company is the company is already using the company's accounting informationsystem but not yet optimal and integrated, so the company experienced problems in purchasing, inventory and cash sales. This includes systems that can help to document each transaction on cash purchases and sales cycle, as well as the inventory cycle system that is not running properly. Expectations of this study, the evaluation of accounting system will facilitate the work of the purchasing department, warehouse, finance and accounting and sales departments in managing the time spent in the operations of the company. This will provide benefits in thepreparation of reports by management in terms of accuracy and speed reports for faster and accurate decisionmaking.